2017
DOI: 10.1007/s40843-017-9024-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicycle photocatalytic reduction of Cr(VI) over transparent PVA/TiO2 nanocomposite films under visible light

Abstract: Photocatalytic reduction of hexavalent chromium in wastewater has been widely investigated as an attractive treatment method. In this work, we reported an efficient method for photocatalytic reduction of Cr(VI) over transparent polyvinyl alcohol/titanium dioxide (PVA/TiO2) nanocomposite films under sunlight irradiation. The transparent PVA/TiO2 nanocomposite films were prepared by a simple hydrothermal method combined with a solution casting process. The results revealed that the anatase TiO2 nanoparticles wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…23 Beside the main peak, a shoulder peak at 688.2 eV appears in the B-TiO 2 -2.0, demonstrating the substitution of F atoms for O atoms in TiO 2 lattices. 24,25 Recent research work has reported that uoride anion is efficient for the stabilization of reduced TiO 2 because of its tendency to form a strong bond with the surface Ti atoms. 26 Moreover, uorine-occupied surface oxygen vacancies can maintain the intrinsic nature of the defects.…”
Section: Resultsmentioning
confidence: 99%
“…23 Beside the main peak, a shoulder peak at 688.2 eV appears in the B-TiO 2 -2.0, demonstrating the substitution of F atoms for O atoms in TiO 2 lattices. 24,25 Recent research work has reported that uoride anion is efficient for the stabilization of reduced TiO 2 because of its tendency to form a strong bond with the surface Ti atoms. 26 Moreover, uorine-occupied surface oxygen vacancies can maintain the intrinsic nature of the defects.…”
Section: Resultsmentioning
confidence: 99%
“…The pH values of the reacting systems were adjusted with HNO 3 to 2. [25] The typical reactions for photocatalytic reductions of K 2 Cr 2 O 7 by TiO 2 are generally considered as following [26] h response to the light over 400 nm. The reusability of NS for the cyclic photocatalytic reduction of Cr (VI) was tested under FL irradiation.…”
Section: Photocatalysismentioning
confidence: 99%
“…A highly crystallized PVA hydrogel has low swelling property, making it desirable for specific biomedical and pharmaceutical applications [4][5][6]. Different studies have shown the notable performance of PVA hydrogel and its composites for wound healing [7], sensors and electrodes [8,9], tissue engineering [10][11][12] and biomedical applications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%